Under the Banner of Islam: Mobilising Religious Identities in West Java - Newland, Lynda (The Australian journal of anthropology, 2000)
Although it is usually claimed that 90% of Indonesians are Muslims, many scholars have characterised Indonesian Islam as ‘not really’ Islam but as only nominally or syncretically so. This paper provides a critique of Clifford Geertz's use of the notion of syncretism followed by a description of the Muslim world as lived by Sundanese villagers in the Priangan Mountains of West Java. Mobilised in response to specific historical conditions, the Sundanese identification with Islam positions the villagers in an ambivalent relation to the state and its discourses of modernity. This relationship is more complicated by the divisions within Islam, broadly between modernist and traditionalist organisations such as Persis and Nahdatul Ulama. While the followers of Persis desire the purification of Muslim practice from local accretions through a return to direct interpretation of the Qur'an, the followers of Nahdatul Ulama interpret the scriptures through the studies of religious scholars which allows for a much broader range of practice. Consequently, notions of nominalism or syncretism have contemporary political ramifications for local arguments concerning the nature of Islam, involving not just philosophical debate but the politicisation of everyday practice.